On the properties of vacancies in solid 4 He as studied by pressure measurements - Remeijer, P.; Steel, S. C.; Jochemsen, R.; Frossati, G.; Goodkind, J. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
We have measured the temperature dependence of the pressure at constant volume in solid 4He in the low density hcp phase. The measurements are analysed in terms of a localized vacancy model and the free Bose gas model of vacancies in solid helium. The results agree better with the free Bose gas model. Within this model we have determined the effective mass of the vacancies to be 3-5 times the bare mass of a 4He atom, corresponding to a bandwidth of 1.3-2.1 K